Experimental Investigation of Material Removal Rate Parameters in ECM for Aluminum Hybrid Matrix Composites Using the RSM Technique. (1st February 2023) - Naga Swapna Sri, M.; Anusha, P.; Rajendranrao Krishnajirao, Vittel Rao; Selvaraj, Manickam; Muthuvel, B.; Karthikeyan, N.
Abstract : In the present work, the preparation of AA-6082/ZrSiO4 /TiC hybrid composite is studied along with an analysis of the effects of electrochemical machining parameters such as feed rate of electrode (FE), voltage (VO), electrolyte concentration (EL), and electrolyte discharge (ED) rate on the output responses of the material removal rate (MRR) and surface roughness (SR) for Al hybrid composites. The experiments are carried out based on the Taguchi L16 orthogonal array and the important process parameters are found for MRR and SR. Each parameter contains four different levels that are FE (0.10, 0.15, 0.20, and 0.25 mm/min), VO (10, 15, 20, and 25 V), EL (15, 20, 25, and 30 g/lit), and ED (1.5, 2, 2.5, and 3 lit/min).The optimization software, namely, Minitab-17 version helps to find the contribution of each parameter on MRR and SR. The ANOVA result reveals that the feed rate of electrode is the highest contributing parameter, trailed by the electrolyte discharge rate and other process parameters for MRR and SR. A linear model of regression and interaction plots is also included to show the relationship between the parameters. From the observational results, the highest MRR (0.00953 mg/min) is attained by the parameter combination level of the feed rate of electrode of 0.20 mm/min, voltage of 25 V, electrolyte concentration of 20 g/lit, and electrolyte discharge rate of 1.5 g/, whereas the lowest MRR is found at FE of 0.10 mm/min, VO of 10 V EL-15 g/lit and ED of 2.5 g/litre. For SR, the maximum and minimum are recognized at FE2-VO4-EL3-ED2 (0.15 mm/min, 25 V, 25 g/lit, and 2 lit/min) and FE1-VO1-EL1-ED1 (0.10 mm/min, 10 V, 15 g/lit, and 1.5 lit/min), respectively. Finally, the increment of MRR and SR values is mostly dependent on the feed rate of the electrode.